PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI KANTOR CABANG BPJS KETENAGAKERJAAN JUANDA SAMARINDA - Thomas, Wilson; Mushofa, Ali; Akhmadi, Akhmadi (OBOR: Oikonomia Borneo, 2022)
Abstract-The purpose of this study is to find out how the influence of leadership and communication toward employee`s performance at Employment BPJS Branch Office Juanda Samarinda. This research use descriptive quantitative methode. Sources of data that used in this research are primary data and secondary data with several of data collecting techniques ; observation, interview, questionnaire. Total of sample in this research is 41 respondent taken by saturated sampling. Statistic methode that used in this research is multiple linear regression analysis supported by SPSS version 16. The result of this research shows partially that Variable of Leadership has positive effectand significant on employee`s performance at Employment BPJS Branch Office Juanda Samarinda and Variable of communication has positive effect on employee`s performance but not significant. Silmutaneously, leadership and communication has positive effect and significant toward employee`s performance at Empoyment BPJS Branch Office Juanda Samarinda. The value of adjused R square is total 0.440 which means every of independent variables able to explain 40% toward dependent variable, while the rest of 56% can be explained influenced by another factors that not being test in this research.